Perkembangan Gerak Dasar Anak di Masa Pandemi - Nur mela Farepsi; Dadan Dadan Suryana (Jurnal Kajian Anak (J-Sanak), 2022)
This study aims to determine the development of children's basic movements during the covid-19 pandemic at TK Negeri Pembina Lengayang. This type of research is descriptive qualitative. The research subjects are B1 class children's. Data collection technique followed the steps of Miles Huberman , namaely; 1) data collection, 2) data reduction, 3) data presentation and 4) verification. While the data validation technique used is a triangulation technique. The results of the study show that, first the basic movements during the covid-19 pandemic in the coach is focused on lokomotor, movements and manipulative movements. Second, the teacher stimulates children's basic movements with gymnastics, games during the pandemic in learning activities. It can be concluded that children's basic movements continue to develop during the pandemic, but not all are stimulated properly. Keywords: Child's basic movement, Covid-19 pandemic